2005
DOI: 10.1007/bf03403685
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Under-reporting Rate for Infectious Gastrointestinal Illness in Ontario

Abstract: Background: In Ontario, infectious gastrointestinal illness (IGI) reporting can be represented by a linear model of several sequential steps required for a case to be captured in the provincial reportable disease surveillance system. Since reportable enteric data are known to represent only a small fraction of the total IGI in the community, the objective of this study was to estimate the under-reporting rate for IGI in Ontario.Methods: A distribution of plausible values for the under-reporting rate was estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 17 publications
2
56
1
Order By: Relevance
“…Relying on evidence from laboratory testing of stool specimens is limited by several factors, as follows ( Moe, 2001 ): an infection may not produce symptoms, an infected person may not seek medical attention, the healthcare provider may not take a stool specimen or the patient may not provide one, the appropriate laboratory test may not be requested, the test may be done incorrectly or may be unable to detect pathogens present, and the laboratory may not report the result in a timely manner or at all. A study of underreporting of gastrointestinal disease in Ontario, Canada ( Majowicz et al, 2005 ), estimated that, for each case reported to the province, there was an estimated median of 285 cases in the community (range 195 to 555). In this analysis, 67 cases were estimated to visit a physician, 17 had a stool sample requested, 14 were submitted, 13 were analyzed, and only 1.5 tested positive.…”
Section: Discussionmentioning
confidence: 99%
“…Relying on evidence from laboratory testing of stool specimens is limited by several factors, as follows ( Moe, 2001 ): an infection may not produce symptoms, an infected person may not seek medical attention, the healthcare provider may not take a stool specimen or the patient may not provide one, the appropriate laboratory test may not be requested, the test may be done incorrectly or may be unable to detect pathogens present, and the laboratory may not report the result in a timely manner or at all. A study of underreporting of gastrointestinal disease in Ontario, Canada ( Majowicz et al, 2005 ), estimated that, for each case reported to the province, there was an estimated median of 285 cases in the community (range 195 to 555). In this analysis, 67 cases were estimated to visit a physician, 17 had a stool sample requested, 14 were submitted, 13 were analyzed, and only 1.5 tested positive.…”
Section: Discussionmentioning
confidence: 99%
“…When national estimates are determined, they must take into account the burden of illness that is not ascertained by routine surveillance. Because many patients with acute gastroenteritis do not visit a health care provider or do not submit a specimen for laboratory testing [5,6,23,24], clinical and laboratoryconfirmed diagnoses greatly underestimate the burden of illness in the community. When the burden of acute gastroenteritis is known, food-specific and pathogen-specific estimates can be calculated.…”
Section: Discussionmentioning
confidence: 99%
“…The public health reporting study focused on reporting practices at the health-unit level. Based on these studies, it was calculated that each case of acute gastroenteritis reported to the Provincial Health Authority represented between 105 and 1389 community cases, with a mean of 313 cases [23].…”
Section: National Initiativesmentioning
confidence: 99%
“…Under-reporting is a problem in reportable disease data (1)(2)(3)(8)(9)(10)(11)(12)(13)(14)(15)(16), and the rates calculated for the present study are based on reported cases. Recent work (8) at the national level estimated the number of community cases of salmonellosis, campylobacteriosis and VTEC infection that can be expected per case reported nationally.…”
Section: Oa Outbreak Associated; Vtec Verotoxigenic Escherichia Coli;mentioning
confidence: 99%